Preparation of magnetic rice husk carbon nanocomposite for efficiently extracting aflatoxin B1 from rice followed by time-resolved fluorescent immunochromatographic assay - Di Yuan; Bin Hong; Shan Zhang; Shan Shan; Jingyi Zhang; Chuanying Ren (Food Chemistry: X)
Abstracts: An on-site, sensitive, and cost-effective method for determining aflatoxin B1 (AFB1) in rice samples is proposed, combining magnetic solid phase extraction (MSPE) and time-resolved fluorescence immunochromatography (TRFICA) techniques. Cost-effective rice husks were carbonized and combined with nanomaterials to make magnetic nanocomposites that acted as effective adsorbents in MSPE. Under optimal conditions, the entire process was completed in 15 min with a visual detection limit of 0.16 μg/kg. Recoveries ranged from 85.2 % to 109.4 %, with intra- and inter-day precisions below 11.5 %. The proposed MSPE-TRFICA method offers a viable alternative for the rapid and highly sensitive quantitative detection of AFB1 for quality assurance.